2016
DOI: 10.3390/educsci6030027
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Practice in Healthcare Education: An Umbrella Review

Abstract: Reflection in healthcare education is an emerging topic with many recently published studies and reviews. This current systematic review of reviews (umbrella review) of this field explores the following aspects: which definitions and models are currently in use; how reflection impacts design, evaluation, and assessment; and what future challenges must be addressed. Nineteen reviews satisfying the inclusion criteria were identified. Emerging themes include the following: reflection is currently regarded as self… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 61 publications
(111 reference statements)
0
80
0
2
Order By: Relevance
“…Further, these projects have not made use of research in medical education for students, which has highlighted the effectiveness of critical reflection and self reflection as methods to improve attitudes, beliefs, understanding of a subject and satisfaction in learning. A number of reflective techniques used in healthcare education have been associated with these improvements, particularly critical reflection [15]. Critical reflection is defined as the emotional and intellectual activity through which people critically assess content, and process information to interpret and give meaning to an experience [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, these projects have not made use of research in medical education for students, which has highlighted the effectiveness of critical reflection and self reflection as methods to improve attitudes, beliefs, understanding of a subject and satisfaction in learning. A number of reflective techniques used in healthcare education have been associated with these improvements, particularly critical reflection [15]. Critical reflection is defined as the emotional and intellectual activity through which people critically assess content, and process information to interpret and give meaning to an experience [16].…”
Section: Introductionmentioning
confidence: 99%
“…Critical reflection is defined as the emotional and intellectual activity through which people critically assess content, and process information to interpret and give meaning to an experience [16]. Critical reflection is part of a model of learning called reflective practice, which has been frequently used in healthcare education over the last decade [15, 17]. In addition reflection is shown to be positively associated with attitudes, beliefs and understanding [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although reflection is very much linked with healthcare education already (Buckley et al 2009;Chaffey et al 2012;Chen and Forbes 2014;Crowe and O'Malley 2006;Epp 2008;Fragkos 2016;Jayatilleke and Mackie 2013;Kuiper and Pesut 2004;Lethbridge et al 2011;Mann et al 2009;McGillivray et al 2015;Miraglia and Asselin 2015;Ng et al 2015;Nguyen et al 2014;Norrie et al 2012;Prasko et al 2012;Rushmer et al 2004;Tsingos et al 2015a;Tsingos et al 2015b;Van Roy et al 2015;Williams 2001), I will try to focus on self-reflection which will improve personal practice as a teacher educator.…”
Section: Contextual Example Contextual Examplementioning
confidence: 99%
“…In other words, there has been an observed disparity between learning and then professional practice. Frenk et al (2010) have demonstrated that there is a mismatch between professional competencies and patient and population priorities, resulting from fragmentary, outdated, and static curricula that produce ill-equipped graduates from underfinanced institutions (Fragkos 2016). …”
Section: Contextual Example Contextual Examplementioning
confidence: 99%
See 1 more Smart Citation